A study on catchment characteristics in Pahang - Ain Amira, Abd Rahim (2014)
Flood risks in Malaysia are increasing due to urbanization which is the continued development of already densely populated flood plains, encroachment on flood-prone areas, destruction of forests and hill slope development. The urbanization processes decrease the infiltratioii process of the rainfall and increase the volume of surface runoff flowing towards the drainage system. When the runoff discharge is higher than the design peak discharge for an urban drainage system, flood will occur. Since Pahang state is an urban catchment, it is facing high risks of flooding. Catchment is an initiative of the Department of Irrigation and Drainage ( JPS ) to overcome the flood particularly in urban and developing areas. The main function of the catchment area is to regulate the flow rate after development that is under the permissible level for management purposes or flood forecasting. Objectives of this study are to identify the characteristics of the catchment area, and the factors that influenced the effectiveness of the watershed as well as to identify the boundaries of the watershed in the state of Pahang. Site is being surveyed by observing the land use. By using GIS, the catchment area and boundaries in the state of Pahang can be obtained. Characteristics of the catchment were analyzed based on three main features such as catchment boundaries, stream length, and pervious and impervious area. These catchment characteristics can be obtained through the topography map and satelite study. As we know that, every region has an area and different types of topography. All data and information required for the study was obtained from the local authorities in the Pahang state. From the data collected, Pahang state has a lot of catchments that need to be preserved to ensure that each catchment can fulfill its function as catchment areas.